SEBUAH STUDI FENOMENOLOGI: AKUNTANSI RUMAH TANGGA DALAM PENGELOLAAN KEUANGAN KELUARGA SAKINAH - Kirana, Andi Aflaha Mulia; Muchlis, Mustakim; Fajrin, Farid (ISAFIR: Islamic Accounting and Finance Review, 2024)
Abstract, This research seeks to examine the experience of how Muslim families manage their finances to achieve harmonious family financial management and find out how household accounting is used within them. This research uses qualitative methods with a descriptive phenomenological approach. Data collection was carried out using observation methods, in-depth interviews, documentation, literature study and internal searching. The data analysis carried out in this research was data transcription of what was obtained from recorded interviews, horizonalization, intentional analysis, bracketing and writing down a series of informants' experiences. The data validity tests used are credibility, transferability, dependability and confirmability tests. The results of this research show that they implement most of the components of family financial management with the aim of achieving sakinah. Even though they have not yet fully implemented household accounting, the family financial management model built by the informants based on religious knowledge is able to make them in a peaceful state in terms of their respective finances. Keywords: Accounting; household accounting; financial management; family sakinah